Guideline‐directed medical therapy in patients undergoing transcatheter edge‐to‐edge repair for secondary mitral regurgitation. (27th July 2022) - Higuchi, Satoshi; Orban, Mathias; Adamo, Marianna; Giannini, Cristina; Melica, Bruno; Karam, Nicole; Praz, Fabien; Kalbacher, Daniel; Koell, Benedikt; Stolz, Lukas; Braun, Daniel; Näbauer, Michael; et al.
Abstract : Aims: Guideline‐directed medical therapy (GDMT), based on the combination of beta‐blockers (BB), renin–angiotensin system inhibitors (RASI), and mineralocorticoid receptor antagonists (MRA), is known to have a major impact on the outcome of patients with heart failure with reduced ejection fraction (HFrEF). Although GDMT is recommended prior to mitral valve transcatheter edge‐to‐edge repair (M‐TEER), not all patients tolerate it. We studied the association of GDMT prescription with survival in HFrEF patients undergoing M‐TEER for secondary mitral regurgitation (SMR). Methods and results: EuroSMR, a European multicentre registry, included SMR patients with left ventricular ejection fraction <50%. The outcome was 2‐year all‐cause mortality. Of 1344 patients, BB, RASI, and MRA were prescribed in 1169 (87%), 1012 (75%), and 765 (57%) patients at the time of M‐TEER, respectively. Triple GDMT prescription was associated with a lower 2‐year all‐cause mortality compared to non‐triple GDMT (hazard ratio [HR] 0.74; 95% confidence interval [CI] 0.60–0.91). The association persisted in patients with glomerular filtration rate <30 ml/min, ischaemic aetiology, or right ventricular dysfunction. Further, a positive impact of triple GDMT prescription on survival was observed in patients with residual mitral regurgitation of ≥2+ (HR 0.62; 95% CI 0.44–0.86), but not in patients with residual mitral regurgitation of ≤1+ (HR 0.83; 95% CI 0.64–1.08). Conclusion: Triple GDMT prescription is associated with higher 2‐year survival after M‐TEER in HFrEF patients with SMR. This association was consistent also in patients with major comorbidities or non‐optimal results after M‐TEER. Abstract : Triple guideline‐directed medical therapy (GDMT) prescription was associated with a lower 2‐year mortality compared to non‐triple GDMT prescription ( A ). Such association was observed in patients with concomitant comorbidities ( B ). CI, confidence interval; CKD, chronic kidney disease; CMP, cardiomyopathy; HR, hazard ratio; MRA, mineralocorticoid receptor antagonists; M‐TEER, mitral valve transcatheter edge‐to‐edge repair; RAS, renin–angiotensin system; ResMR, residual mitral regurgitation; RV‐Dys, right ventricular dysfunction; SMR, secondary mitral regurgitation.